Rotavirus infection in Neonatal Intermediate Care Unit - Hilda G. Hernández-Orozco; Guadalupe L. Aparicio-Santiago; Esperanza Lucas-Reséndiz; José Luis Castañeda-Narváez; Carlos López-Candiani; Virginia Díaz-Jiménez; Aurora Rosas-Ruiz; Ma. del Carmen Sandoval-Medina; Patricia Arzate-Barbosa; Wendy Domínguez-Viveros; Patrik Eliana Sarmiento-Wilches (Instituto Nacional de Pediatría, 2014)
Rotavirus acute gastroenteritis, continues to be one of the most common cause of morbidity in children younger than 2 years of age. However, it is not often to report outbreaks in neonatal intensive care units. The aim of this paper was to describe the epidemiological investigation of a Rotavirus outbreak, the viral transmission between infants and the control measures taken. Materials and Methods: An outbrake study was performed in a neonatal intermediate care unit due to the presence of Rotavirus gastroenteritis cases. Results: We identified 3 rotavirus gastroenteritis cases confirmed by direct antigen detection, the source could not be identified. Discussion: We considered a transmission mechanism of propagated source because infected people excreted large number of viral particles and cause widespread environmental contamination. Conclusion: Quickly case identification and implemented implemen- tation of control measures prevent new cases and limits the spread of the outbreak.